Frequency of expression and generation of T-cell responses against antigens on multiple myeloma cells in patients included in the GMMG-MM5 trial - Schmitt, Michael; Hückelhoven-Krauss, Angela; Hundemer, Michael; Schmitt, Anita; Lipp, Susanne; Emde-Rajaratnam, Martina; Salwender, Hans; Hänel, Mathias; Weisel, Katja; Bertsch, Uta; Dürig, Jan; Ho, Anthony Dick; et al. (OncoTarget, 2017)
Background: Raising T-cell response against antigens either expressed on normal and malignant plasma cells (e.g. HM1.24) or aberrantly on myeloma cells only (e.g. cancer testis antigens, CTA) by vaccination is a potential treatment approach for multiple myeloma. Results Expression by GEP is found for HM1.24 in all, HMMR in 318/458 (69.4%), MAGE-A3 in 209/458 (45.6%), NY-ESO-1/2 in 40/458 (8.7%), and WT-1 in 4/458 (0.8%) of samples with the pattern being confirmed by RNA-sequencing. T-cell-activation is found in 9/26 (34.6%) of patient samples, i.e. against HM1.24 (4/24), RHAMM-R3 (3/26), RHAMM1-8 (2/14), WT-1 (1/11), NY-ESO-1/2 (1/9), and MAGE-A3 (2/8). In 7/19 T-cell activation responses, myeloma cells lack respective antigen-expression. Expression of MAGE-A3, HMMR and NY-ESO-1/2 is associated with adverse survival. Experimental design: We assessed expression of HM1.24 and the CTAs MAGE-A3, NY-ESO-1/2, WT-1 and HMMR in CD138-purified myeloma cell samples of previously untreated myeloma patients in the GMMG-MM5 multicenter-trial by gene expression profiling (GEP; n = 458) and RNA-sequencing (n = 152) as potential population regarding vaccination trials. We then validated the feasibility to generate T-cell responses (n = 72) against these antigens by IFN-γ EliSpot-assay (n = 26) related to antigen expression (n = 22). Lastly, we assessed survival impact of antigen expression in an independent cohort of 247 patients treated by high-dose therapy and autologous stem cell transplantation. Conclusions: As T-cell responses can only be raised in a subfraction of patients despite antigen expression, and the number of responses increases with more antigens used, vaccination strategies should assess patients’ antigen expression and use a “cocktail” of peptide vaccines.